Estudio de factibilidad para la comercialización de equipos tecnológicos y servicio técnico en el distrito de Buenaventura (2014)
The present work is a model for feasibility studies whose results offer alternatives to promote technology in the city of Buenaventura and it offers integrated specialized service by category, as well as providing great benefits of training, becoming future not only in marketing, but in training center for technicians and students. Among the topics covered in the following feasibility study, various studies such as market, technical, administrative, legal, for which the use of the various types of research such as descriptive research was needed where cover inductive methods, equally necessary statistical methods were used when ordering, classifying and interpreting the data obtained was used. During the development of this text the use of all information acquired during the training stage, which is to contribute to meeting the needs of maintenance and technology in the city was necessary, may also provide the opportunity to generate employment and improving the quality of life of its inhabitants. This document reflects the need and response so that its feasibility is demonstrated in the creation of a technology company is given, which has been a goal for the future which ends today.